A jóhiszeműség és tisztesség magánjogi alapelve erényetikai paradigmában - Benke, József (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
In the exercise of rights and in the performance of duties, the requirement of good faith and fair dealing encompasses the entire Hungarian legal system. In private law, including business relations, it has absolute priority. The exact determination of the content of the principle codified in Art. 1:3(1) of the Hungarian Civil Code required not only grammatic-logical and systematic-authentic interpretation but necessitated also a historical and comparative legal analysis. However, the usual, complex interpretation of norms could not lead to the pragmatically desirable result that the courts applying the codified norm do need. In order to achieve this goal, it was inevitable to examine in particular the treasures handed down to us from the philosophical, legal and religious-ethical intellectual complexes of the European intellectual heritage. As a result of the analysis, it is found that the conduct meets the requirement of the codified principle of good faith and fair dealing, which realizes the following four values [see I)-IV)] within the framework of the following five limiting factors [see 1)-5)]. The limitations are: 1) the interdependence of juxtaposition and equality; 2) the degree of objective rationality; 3) consideration of the other party's legal interest or interest worthy of consideration in addition to one’s own legal interest; 4) the general customs and practices between the parties; and 5) the frameworks of justice and equity. Between these frames, the legal subject makes the following: I) does good, avoids bad; II) does to the other what he also wishes for himself; III) does not hurt the others, IV) gives to others what they owe.